Improving Higher Education Performance Through Strategic Collaboration And Intellectual Capital: A Path To Competitive Advantage - Irsan Aras; Iskandar A A; Andala Rama Putra Barusman; Defrizal Defrizal (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research aims to explore how strategic collaboration and intellectual capital can improve higher education performance and achieve competitive advantage. The main objective of this study is to identify the relationship between strategic collaboration, intellectual capital, and the performance of higher education institutions, as well as how these three elements can be used synergistically to achieve competitive advantage. The research method used is a quantitative approach with the population of all private universities (PTS) in the LLDikti II Region, which totals 197 private universities. The data analysis technique uses the Structural Equation Models (SEM) approach with the help of the SmartPLS program package. The results of the study show that strategic collaboration has a positive and significant impact on higher education performance. In addition, intellectual capital was also found to contribute significantly to improving the performance of the institution. The combination of strategic collaboration and intellectual capital resulted in a greater improvement in higher education performance compared to each element separately. These results show that institutions that adopt a collaborative approach and manage their intellectual capital will tend to have better performance and are able to compete more effectively in the global education market. Based on these findings, the study recommends that higher education institutions should increase their collaborative efforts, both inside and outside the institution, as well as invest in the development and management of intellectual capital.